Etiology of Diarrhea in Older Children, Adolescents and Adults: A Systematic Review - Fischer Walker, Christa L. (Public Library of Science, 2010)
BACKGROUND: Diarrhea is an important cause of morbidity and mortality in all regions of the world and among all ages, yet little is known about the fraction of diarrhea episodes and deaths due to each pathogen. METHODOLOGY/PRINCIPAL FINDINGS: We conducted a systematic literature review to identify all papers reporting the proportion of diarrhea episodes with positive laboratory tests for at least one pathogen in inpatient, outpatient and community settings that met our inclusion and exclusion criteria. We identified a total of 25,701 papers with possible etiology data and after final screening included 22 papers that met all inclusion and exclusion criteria. Enterotoxigenic Escherichia coli and V. cholerae O1/O139 were the leading causes of hospitalizations. In outpatient settings, Salmonella spp., Shigella spp., and E. histolytica were the most frequently isolated pathogens. CONCLUSIONS/SIGNIFICANCE: This is the first systematic review which has considered the relative importance of multiple diarrhea pathogens. The few studies identified suggest that there is a great need for additional prospective studies around the world in these age groups to better understand the burden of disease and the variation by region.